Numerical and experimental examination of the retention of magnetic nanoparticles in magnetic chromatography. (1st May 2021) - Marquardt, Jan E.; Arlt, Carsten-Rene; Trunk, Robin; Franzreb, Matthias; Krause, Mathias J.
Abstract: This paper investigates a promising new approach of magnetic chromatography to improve particle fractionation in industrial-scale production. To understand the still challenging multidimensional separation mechanism, we develop a novel method to simulate magnetic nanoparticles' behavior in a magnetized chromatographic column based on a lattice Boltzmann method. In contrast to conventional numerical studies, the Euler–Euler approach is applied by utilizing the advection–diffusion equation to describe the particle component. As a result, the consideration of the magnetic force, the drag force, and a realistic diffusion are possible. Also, enormous computational costs are saved. We show that the column can be modeled from a combination of two unit cells, and a separation effect can be detected even with small magnetic fields. Furthermore, we compare the numerical results to practical experiments. Both results are in good accordance. We additionally determine potential improvements. Besides improving the setup by using stronger magnetic fields, the structure of the column's matrix plays an important role. Thus, we find that higher porosity leads to higher retention times. Highlights: Euler–Euler approach utilizing a lattice Boltzmann method. Consideration of real diffusion as well as magnetic and drag force. Numerical investigation of particle fractionation utilizing magnetic chromatography. Comparison to practical experiments shows good accordance of the results.